2003
DOI: 10.1007/s11746-003-0829-3
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and growing location effects on phytosterols in canola oil

Abstract: There is little information available about phytosterols in canola (Brassica napa L.) oil and the effects of genotype and growing locations from Virginia and the mid-Atlantic region of the United States, a potential area for the establishment of domestic production to provide edible oil. Our objectives were to characterize the phytosterols, phospholipids, unsaponifiable matter, and FA in oil from Virginia-grown canola. Among 11 canola genotypes grown at two locations during 1995-1996 significant variations exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
52
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 16 publications
12
52
1
2
Order By: Relevance
“…It also contained 0.5~1.1% phytosterols which are consisted of 55~58% β-sitosterol, 20~29% campesteol, 5~13% brassicasterol and <5% stigmasterol (Hamama et al 2003). Similar results were observed in this study where γ-tocopherol was found to be a major tocopherol (over 80%), and β-sitosterol (over 55%) as a major phytosterol in eight Korean rapeseed varieties (Table 5).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…It also contained 0.5~1.1% phytosterols which are consisted of 55~58% β-sitosterol, 20~29% campesteol, 5~13% brassicasterol and <5% stigmasterol (Hamama et al 2003). Similar results were observed in this study where γ-tocopherol was found to be a major tocopherol (over 80%), and β-sitosterol (over 55%) as a major phytosterol in eight Korean rapeseed varieties (Table 5).…”
Section: Resultssupporting
confidence: 85%
“…Tocopherols have been recognized as a classic free radical scavenger with chain-breaking properties and are one of the most important fat-soluble antioxidants in biological systems (Prabhudas et al 2000;Alpaslan & Gunduz 2000). Rapeseed oil commonly contains about 0.5~1.1% phytosterols which are consisted of 55~58% sitosterol, 20~29% campesteol, 5~13% brassicasterol and <5% stigmasterol (Hamama et al 2003). Phytosterols are minor constituents of vegetable oils, cereals seed, nuts, and fruits, and their concentrations vary according to plant species (Ostlund 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Increased phytosterol content in oilseed rape could constitute an added value to oil and its derivatives. In the two populations of winter oilseed rape studied the phytosterol content of each turned out to be higher than in the work of Hamama et al (2003), although the corresponding compounds were all in the similar propotion. Amar et al (2008a) reported a variation in total phytosterol content ranging from 2570 to 4150 mg/kg seed for three diff erent doubled haploid populations of winter oilseed rape tested in fi eld experiments.…”
Section: Phytosterol Contentmentioning
confidence: 59%
“…Among these, oilseed rape has been identifi ed as the one with the highest content (Amar et al, 2008a). In Brassica napus a large part of phytosterols comprises β-sitosterol (45-58%) and campesterol (25-39%), followed by brassicasterol and avenasterol, with stigmasterol occurring in small quantities (Hamama et al, 2003;Nogala-Kałucka et al, 2005). Increased phytosterol content in oilseed rape could constitute an added value to oil and its derivatives.…”
Section: Phytosterol Contentmentioning
confidence: 99%
See 1 more Smart Citation